Losses, Many‐Body Correlations, and Universality in Ultracold Molecules. Issue 4 (20th February 2022) - He, Mingyuan; Lv, Chenwei; Zhou, Qi
Abstract: Recent experimental developments have allowed physicists to freeze molecules' motion down to an ultracold temperature regime where quantum effects become profound. Furthermore, each molecule can be precisely prepared at chosen internal states and the mutual interactions between molecules are also highly tunable. As such, ultracold molecules have emerged as a powerful platform in multiple disciplines across physics and chemistry. Meanwhile, a grand challenge exists as to how losses of molecules depend on a quantum many‐body environment. In this article, the recent experimental and theoretical progress of exploring losses of ultracold molecules is reviewed. Since the conventional theoretical scheme of treating isolated pairs of molecules is no longer applicable to the quantum degenerate regime that has been reached in recent experiments, an alternative framework of universal relations between two‐body losses and many‐body correlations has been established. Regardless of microscopic parameters ranging from the temperature and the particle number to the interaction strength, these universal relations always hold. This approach unfolds a simple universality behind complex loss processes of many‐body systems and provides physicists and chemists with a new tool to explore ultracold molecules. Abstract : In this article, recent experimental and theoretical progress in the study of ultracold molecules is reviewed. Responding to a great challenge raised by recent experiments, it is discussed how a new framework of universal relations concerning reactions in a quantum many‐body environment has been established. Possible future directions are also discussed.